A Tribute to Barney Glaser (1930-2022) - Olavur Christiansen (Grounded Theory Review: An International Journal, 2007)
The inductive methodology of classic grounded theory (CGT) is extremely different from the logical-deductive methodology of mainstream economics - as well as the inductive econometrics approach. Consequently, it becomes a pressing issue how Barney Glaser’s work an be used in the contexts of economic. To use CGT on an abstract concept like “mainstream economics” would be an impossibility. A CGT is about the behaviour of some specific individuals - as for example groups of economic practitioners. These practitioners should be a fairly homogenous group of people – a collective of university economists and business professionals might be too heterogeneous. Thus, it is suggested that a CGT is carried out for each homogenous group of economic practitioners, and that an attempt subsequently is made to generate a formal (higher-level) CGT that covers all these groups. The main principles of CGT are briefly explained with the purpose of demonstrating the generation of a CGT in microeconomics, and how the core variable of a CGT of macroeconomics can be allowed to emerge.